Regeneration patterns of multicultural values in the Muneng Pilgrimage Tradition in Temanggung, Indonesia - Anggraeni, Laela Dian; Supriadi, Didik (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research answers regeneration patterns and multicultural values ​​in the Muneng pilgrimage tradition. Introducing traditions to the younger generation is very important. Society cannot avoid generations because these habits are inherent and have their own meaning for a society. The results of this research show that the regeneration carried out in the Muneng pilgrimage tradition culture needs to include regeneration of cultural presenters, cultural implementers and cultural viewers. The methods used are the value of respect, the value of tolerance, the value of respect, the value of cooperation. This research aims to describe the multicultural values ​​of the Muneng pilgrimage tradition. The method used is the historical method. This historical method has steps that include processional heuristics and offerings, criticism in the form of authentic tests rather than external and internal, interpretation of historical analysis, and historiography. The results nclude 1) Regeneration is carried out with the involvement of all ages, 2) The Muneng pilgrimage becomes a motif of belief and becomes a means of preserving culture in Muneng, 3) The values ​​in culture result in harmonization in life.